THE JOURNALIST’S COMMUNITY AND ETHICS CODE IN INDONESIA - Sika Nur Indah (IAIN Salatiga, 2019)
A violation of ethics code reported by some journalists shows that there is a problem in the journalistic ethics code. This research aims to find out the role of journalists community in influencing the knowledge of journalistic ethics code. This qualitative research method done by interviewing some of reporters in Solo, Central Java, Indonesia. The results showed two supportive community groups that support Indonesian journalist code of ethics, Kode Etik Wartawan Indonesia (KEWI) and also did not support it. The first group will help the role of press companies and organisations in providing the knowledge of journalistic ethics code. Meanwhile, the second group maybe will blockage the role of press companies and organisations in providing the knowledge of journalistic ethics code Thus community will becomes one of the important factor for journalists in learning and gaining the knowledge of journalistic ethics code, outside the press company and the press organization